Discrepancies in the Tumor Microenvironment of Spontaneous and Orthotopic Murine Models of Pancreatic Cancer Uncover a New Immunostimulatory Phenotype for B Cells - Spear, Sarah; Candido, Juliana B.; McDermott, Jacqueline R.; Ghirelli, Cristina; Maniati, Eleni; Beers, Stephen A.; Balkwill, Frances R.; Kocher, Hemant M.; Capasso, Melania (Frontiers in Immunology, 2019)
B cells are salient features of pancreatic ductal adenocarcinoma (PDAC) tumors, yet their role in this disease remains controversial. Murine studies have indicated a protumoral role for B cells, whereas clinical data show tumor-infiltrating B cells are a positive prognostic factor, both in PDAC and other cancers. This disparity needs to be clarified in order to develop effective immunotherapies. In this study, we provide new evidence that reconcile human and mouse data and highlight the importance of using relevant preclinical tumor models when assessing B cell function. We compared B cell infiltration and activation in both a genetic model of murine PDAC (KPC mouse) and an injectable orthotopic model. A pronounced B cell infiltrate was only observed in KPC tumors and correlated with T cell infiltration, mirroring human disease. In contrast, orthotopic tumors exhibited a relative paucity of B cells. Accordingly, KPC-derived B cells displayed markers of B cell activation (germinal center entry, B cell memory and plasma cell differentiation) accompanied by significant intratumoral immunoglobulin deposition, a feature markedly weaker in orthotopic tumors. Tumor immunoglobulins, however, did not appear to form immune complexes. Furthermore, in contrast to the current paradigm that tumor B cells are immunosuppressive, when assessed as a bulk population, intratumoral B cells upregulated several proinflammatory and immunostimulatory genes, a distinctly different phenotype to that of splenic-derived B cells; further highlighting the importance of studying tumor-infiltrating B cells over B cells from secondary lymphoid organs. In agreement with the current literature, genetic deletion of B cells (µMT mice) resulted in reduced orthotopic tumor growth, however, this was not recapitulated by treatment with B-cell-depleting anti-CD20 antibody and, more importantly, was not observed in anti-CD20-treated KPC mice. This suggests the result from B cell deficient mice might be caused by their altered immune system, rather than lack of B cells. Therefore, our data indicate B cells do not favor tumor progression. In conclusion, our analysis of relevant preclinical models shows B cells to be active members of the tumor microenvironment, producing immunostimulatory factors that might support the adaptive antitumor immune response, as suggested by human PDAC studies.